2017
DOI: 10.1038/ncomms16047
|View full text |Cite
|
Sign up to set email alerts
|

The ancestral flower of angiosperms and its early diversification

Abstract: Recent advances in molecular phylogenetics and a series of important palaeobotanical discoveries have revolutionized our understanding of angiosperm diversification. Yet, the origin and early evolution of their most characteristic feature, the flower, remains poorly understood. In particular, the structure of the ancestral flower of all living angiosperms is still uncertain. Here we report model-based reconstructions for ancestral flowers at the deepest nodes in the phylogeny of angiosperms, using the largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
344
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(374 citation statements)
references
References 66 publications
14
344
3
Order By: Relevance
“…In Haemodoraceae, there is much variation in the shape of the perianth lobes (Simpson 1990, 1998). Nonetheless, equal perianth lobes seem to be plesiomorphic in the monocots (Sauquet et al 2017; Stevens 2001–onwards) and dominant in the family, being recorded for 11 out of 14 genera (Pellegrini, pers. observ.).…”
Section: Discussionmentioning
confidence: 99%
“…In Haemodoraceae, there is much variation in the shape of the perianth lobes (Simpson 1990, 1998). Nonetheless, equal perianth lobes seem to be plesiomorphic in the monocots (Sauquet et al 2017; Stevens 2001–onwards) and dominant in the family, being recorded for 11 out of 14 genera (Pellegrini, pers. observ.).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has confirmed that the most recent common ancestor (i.e. crown node) of all living angiosperms possessed bisexual flowers with a perianth (Sauquet et al ., ). The most recent common ancestor of seed plants (i.e.…”
Section: Six Key Questionsmentioning
confidence: 99%
“…On the one hand, morphospace approaches have allowed the quantification of differences among taxa or sets of traits (modules) in general integration using multidimensional statistics (Chartier et al ., , ). On the other hand, correlations among key floral traits have been tested using comparative methods that take the phylogeny explicitly into account (O'Meara et al ., ; Sauquet et al ., ).…”
Section: Six Key Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An A/E gymnosperm pro-orthologue gave rise to angiosperm A and E genes, and further duplicated A genes were also retained after the ε WGD 19, 2124 . These duplicated and diversified gene sets organised to generate the first now-extinct flowers, and recent reconstructions suggest that these were bisexual with petal-like tepals and pollen-bearing stamens arranged in multiple concentric whorls, and female carpels in a central spiral 25 . Among living angiosperms, the Amborella lineage evolved a ‘fading borders’ programme, such that the whole flower is a spiral that gradually transitions from bracts to outer then inner tepals (specified by ABc combinations), from inner tepals to stamens (aBC) then carpels (abC), in which upper case indicates functions of greatest influence in the respective organs 26 .…”
Section: Contributions Of Whole-genome Duplications To the Origin Andmentioning
confidence: 99%